Associations between digit ratio (2D:4D) and locus of control. (September 2015) - Richards, Gareth; Stewart-Williams, Steve; Reed, Phil
Highlights: The 2D:4D ratio and directional asymmetry measure prenatal sex-hormone exposure. The current study investigated 2D:4D in relation to locus of control (LoC). Positive correlations between LoC in females and right hand 2D:4D and D(R–L). Concentration and sensitivity to sex hormones may influence development of LoC. Abstract: The relative lengths of the index and ring fingers (2D:4D), as well as the directional asymmetry between the right and left hands [D(R–L)], are putative measures of prenatal sex hormone exposure. The 2D:4D ratio has been associated with a number of personality traits including neuroticism, agreeableness, extraversion, and openness to experience. The current study therefore aimed to build on these findings by investigating 2D:4D in relation to Rotter's (1966) Locus of Control Questionnaire (LoCQ). Significant positive correlations were observed between LoCQ scores in females and right hand 2D:4D and D(R–L), though no such relationships emerged in males. The findings suggest that differences in concentration and/or sensitivity to prenatal sex hormones may play a role in the development of an individual's locus of control.